(untitled) (Global Journal of Human-Social Science, 2011)
Employee retention is the vital challenge in all organizations This papers focus on one industry that is the leather industry of Pakistan which is facing the same problem of retention of employees due to many reasons As Leather industry is the third largest export earning sector in Pakistan so these reasons are discussed in detail The turnover rate in Leather Industry of Pakistan is around 25 30 annually its observed that mostly second line managers change their job s for high salaries offer recognition authority and also to seek for more knowledge and to get more competitive edge in terms of processing In tanneries its critical and alarming because of the process and article secrecy In order to achieve competitive advantage maximum utilization of resources and to get organizational efficiency employees must be retained in a true spirit in order to cope with all these conditions In this paper the authors tried to know the reasons behind this dilemma that how employees can be retained and some suggestions were given to deal with it One edge of this paper is that one of the author belongs to the same industry i e leather industry